Adhesive with high adhesion strength for low-surface-energy materials as well as preparation method and application of adhesive
By using adhesives with hard fluorinated segments and soft segments of long polymer chains, the problem of bonding low-surface energy materials is solved, high adhesion strength and universality are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202510704110.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-29
- Publication Date
- 2025-08-01
AI Technical Summary
The prior art is difficult to effectively bond low-surface energy materials, the traditional methods are complex and expensive, and the non-covalent bonding strength is insufficient.
Adhesives containing fluorinated hard segments and long polymer chain soft segments are used to improve adhesion strength through dipole-dipole interaction and plasticization. The preparation methods include photo-induced or heat-induced polymerization and vacuum drying.
Adhesives with high adhesion strength on low surface energy materials are achieved without surface pretreatment, reducing production costs and providing good universality and bonding strength.
Smart Images

Figure CN120399608A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of materials, and particularly to an adhesive with high adhesion strength for low surface energy materials, its preparation method and uses. Background Art
[0002] Fluoropolymer-based low surface energy (LSE) materials are widely used in various fields due to their unique hydrophobicity, anti-fouling properties and corrosion resistance. However, their low surface energy (usually ≤ 20 mN / m) and chemical inertness make it difficult for traditional adhesives to achieve effective bonding through wetting or chemical bonding. To solve this problem, existing technologies mainly focus on two types of strategies: surface pretreatment technology and non-covalent bonding technology. Surface pretreatment technologies include chemical etching and ion beam / laser treatment. Although they can improve the bonding performance in the short term, they generally have defects such as high process complexity, high cost, and irreversible surface damage. In particular, they may cause functional damage to precision electronic components or flexible medical devices. The non-covalent bonding technology developed in recent years relies on ionic liquid raw materials, which are expensive and the bonding strength is still not ideal, only about 1 MPa. Summary of the Invention
[0003] The purpose of the present application is to provide an adhesive with high adhesion strength for low surface energy materials, its preparation method and uses to solve the above problems.
[0004] To achieve the above purpose, the present application adopts the following technical solutions:
[0005] An adhesive with high adhesion strength for low surface energy materials, comprising a fluorinated hard segment and a long polymer chain soft segment with a plasticizing effect;
[0006] The fluorinated hard segment monomers corresponding to the fluorinated hard segment include fluorinated methacrylate monomers; the soft segment monomers corresponding to the long polymer chain soft segment with a plasticizing effect include polyether-based methacrylate monomers.
[0007] This design concept can be extended to different monomers with the same function, and only need appropriate regulation to show the characteristics of high adhesion on low surface energy substrates.
[0008] Preferably, the fluorinated hard segment monomers include one or more of hexafluorobutyl methacrylate, trifluoroethyl methacrylate, tetrafluoropropyl methacrylate, pentafluorobenzyl methacrylate, hexafluoroisopropyl methacrylate, heptafluorobutyl methacrylate, octafluoropentyl methacrylate, nonafluorohexyl methacrylate, dodecafluoroheptyl methacrylate, tridecafluorooctyl methacrylate, perfluoroalkyl ethyl methacrylate, perfluorooctyl methacrylate, 2-[(1',1',1'-trifluoro-2'-(trifluoromethyl)-2'-hydroxy)propyl]-3-norbornene methacrylate;
[0009] Preferably, the soft segment monomer includes one or more of poly(propylene glycol) methacrylate, methoxypolyethylene glycol methacrylate, methoxypolyethylene glycol acrylate, polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, tetraethylene glycol monomethacrylate, polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate, poly(ethylene glycol) methacrylate, and ethoxylated trimethylolpropane triacrylate.
[0010] Preferably, the mass ratio of the fluorinated hard segment monomer to the soft segment monomer is 1-9:1, preferably 17:3.
[0011] Optionally, the mass ratio of the fluorinated hard segment monomer to the soft segment monomer can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or any value between 1-9:1.
[0012] Preferably, the number average molecular weight range of the adhesive is 268870 g / mol to 2688700 g / mol.
[0013] The present application also provides a method for preparing the adhesive with high adhesion strength to low surface energy materials as described above, including:
[0014] Mixing the fluorinated hard segment monomer, the soft segment monomer, and an initiator to obtain a precursor liquid;
[0015] Performing a polymerization reaction on the degassed precursor liquid, and then drying it under vacuum to obtain the adhesive.
[0016] Preferably, the initiator includes a photoinitiator and / or a thermal initiator;
[0017] The photoinitiator includes one or more of 1-hydroxy-cyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,4,6(trimethylbenzoyl) diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphosphinate, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholin-1-propanone, 2-isopropylthioxanthone, ethyl 4-dimethylaminobenzoate, benzoin dimethyl ether, methyl o-benzoylbenzoate, 4-chlorobenzophenone, 4-phenylbenzophenone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and α-ketoglutaric acid;
[0018] The thermal initiator includes one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptonitrile, dimethyl azobisisobutyrate, 1-(cyano-1-methylethylazo)formamide, 1,1'-azobis(cyanocyclohexane), benzoyl peroxide, diisopropylbenzene peroxide, methyl ethyl ketone peroxide, di-tert-butyl peroxide, potassium persulfate, and ammonium persulfate.
[0019] Preferably, the dosage of the initiator is 0.01%-10% of the total mass of the fluorinated hard segment monomer and the soft segment monomer, preferably 1%.
[0020] Optionally, the dosage of the initiator can be 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% of the total mass of the fluorinated hard segment monomer and the soft segment monomer, or any value between 0.01% and 10%.
[0021] Preferably, the polymerization reaction is photoinitiated, and the conditions for photoinitiation are a light source power density of 1-1000 mW / cm 2 , a wavelength of 200-450 nm, and a time of 0.01-24 h;
[0022] Optionally, the light source power density can be 1 mW / cm 2 , 10 mW / cm 2 , 100 mW / cm 2 , 200 mW / cm 2 , 300 mW / cm 2 , 400 mW / cm 2 , 500 mW / cm 2 , 600 mW / cm 2 , 700 mW / cm 2 , 800 mW / cm 2 , 900 mW / cm 2 , 1000 mW / cm 2 or any value between 1-1000 mW / cm 2 , the wavelength can be 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, or any value between 200-450 nm, and the time can be 0.01 h, 0.05 h, 0.1 h, 0.5 h, 1 h, 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h, or any value between 0.01-24 h;
[0023] or;
[0024] The polymerization reaction is thermally initiated, and the temperature of the thermal initiation is 40 - 110°C, and the time is 1 - 72 h;
[0025] Optionally, the temperature of the thermal initiation can be 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or any value between 40 - 110°C, and the time can be 1 h, 6 h, 12 h, 18 h, 24 h, 30 h, 36 h, 42 h, 48 h, 54 h, 60 h, 66 h, 72 h or any value between 1 - 72 h;
[0026] Alternatively, the polymerization reaction is carried out by the immersion method.
[0027] Preferably, the preparation method of the adhesive having high adhesion strength to low surface energy materials satisfies one or more of the following conditions:
[0028] (1) The conditions for degassing are: vacuum degree 1 - 20 kPa, time 0.1 - 10 min;
[0029] Optionally, the vacuum degree for degassing can be 1 kPa, 5 kPa, 10 kPa, 15 kPa, 20 kPa or any value between 1 - 20 kPa, and the time can be 0.1 min, 0.5 min, 1 min, 5 min, 10 min or any value between 0.1 - 10 min;
[0030] (2) The conditions for vacuum drying are: vacuum degree 0.1 - 1000 Pa, temperature 20 - 100°C, time 18 - 24 h;
[0031] Optionally, the vacuum degree for vacuum drying can be 0.1 Pa, 1 Pa, 10 Pa, 100 Pa, 200 Pa, 300 Pa, 400 Pa, 500 Pa, 600 Pa, 700 Pa, 800 Pa, 900 Pa, 1000 Pa or any value between 0.1 - 1000 Pa, the temperature can be 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or any value between 20 - 100°C, and the time can be 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h or any value between 18 - 24 h;
[0032] (3) The storage conditions for the adhesive are: relative humidity not higher than 60%, temperature -50°C to 60°C.
[0033] Optionally, the stored relative humidity can be any value between 10%, 20%, 30%, 40%, 50%, 60% or not higher than 60%, and the temperature can be -50°C, -40°C, -30°C, -20°C, -10°C, 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C or any value between -50°C and 60°C.
[0034] The present application also provides a use of the adhesive having high adhesion strength to low surface energy materials for bonding low surface energy materials.
[0035] Low surface energy materials are, for example, polytetrafluoroethylene (PTFE), polypropylene (PP), and polyethylene (PE).
[0036] Compared with the prior art, the beneficial effects of the present application include:
[0037] The adhesive provided by the present application, which has high adhesion strength to low surface energy materials, has a fluorinated hard segment and a long polymer chain soft segment with a plasticizing effect. The C-F groups in the fluorinated hard segment monomers have dipole-dipole interactions with the low surface energy material substrate, which improves the adhesion energy of the material to the low surface energy material substrate. In addition, such monomers have a relatively high glass transition temperature, providing high cohesive energy for the adhesive, making the adhesive not easily stress yield due to being too soft; the long polymer chain soft segment monomers with a plasticizing effect have both a plasticizing effect and a long chain structure, which can not only provide a topological structure for dissipating energy through side chain friction, but also avoid the molecular chain rigidity of the hard segment being too strong to cause non-bonding through the plasticizing effect, and at the same time reduce the glass transition temperature of the material, so that the bonding strength reaches the highest value. The adhesive having high adhesion strength to low surface energy materials has excellent bonding strength, does not require surface pretreatment of the material, has good universality, reduces production costs, and provides new ideas for the development of bonding of low surface energy materials.
[0038] The preparation method of the adhesive provided by the present application, which has high adhesion strength to low surface energy materials, is convenient, fast and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the drawings required to be used in the embodiments. It should be understood that the following drawings only show some embodiments of the present application and should not be regarded as limiting the scope of the present application.
[0040] Figure 1 It is a graph showing the influence relationship of different monomer feeding ratios on the lap-shear strength;
[0041] Figure 2 It is a graph showing the relationship between different fluorinated hard segment monomers and the lap-shear strength;
[0042] Figure 3 Relationship diagram of different plasticized long molecular chain soft segment monomers and lap-shear strength;
[0043] Figure 4 Data diagram of lap-shear strength on different substrates;
[0044] Figure 5 Data diagram of the adhesive durability of materials in a high humidity environment;
[0045] Figure 6 Distribution diagram of fluorinated groups at the non-bonding interface of the material;
[0046] Figure 7 Distribution diagram of fluorinated groups at the bonding interface of the material;
[0047] Figure 8 Transparency photo of the material;
[0048] Figure 9 Influence diagram of different feeding ratios of hard segment monomers without fluorinated groups on lap-shear strength;
[0049] Figure 10 Influence diagram of different feeding ratios of soft segment monomers without long side chains on lap-shear strength. Detailed implementation manners
[0050] The following will describe the implementation scheme of the present application in detail in combination with specific embodiments. However, those skilled in the art will understand that the following embodiments are only used to illustrate the present application and should not be regarded as limiting the scope of the present application. For those not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. For the reagents or instruments not specified for the manufacturer, they are all conventional products that can be obtained through commercial purchase.
[0051] Example 1
[0052] This example provides an adhesive, and its preparation method is as follows:
[0053] Mix 3.4 g of hexafluorobutyl methacrylate (fluorinated hard segment monomer, HFBMA), 0.6 g of poly(propylene glycol) methacrylate (plasticized soft segment monomer, PPGMA, Mn 375), and 0.04 g of hydroxy-cyclohexyl phenyl ketone (photoinitiator 184), and stir well until homogeneous to form a precursor solution. Put the uniformly mixed precursor solution into a vacuum chamber with a vacuum degree of 0.1 bar and degas for 30 s. Inject the degassed precursor solution into the assembled glass sheet-silica gel pad-PTFE sandwich cavity. Place the mold injected with the precursor solution in an ultraviolet cross-linking box with a power density of 50 mW / cm 2, polymerize for 30 min. After the reaction is completed, disassemble the silicone pad mold, take out the sample and place it in a vacuum drying oven. Under vacuum at 80 °C, degas for 12 h to remove residual volatile monomers, obtaining a low surface energy and high adhesion polymer adhesive, which is stored at room temperature in a desiccator for later use.
[0054] Example 2
[0055] This example provides an adhesive, and its preparation method is as follows:
[0056] Mix 2.4 g of hexafluorobutyl methacrylate (fluorinated hard segment monomer, HFBMA), 1.6 g of poly(propylene glycol) methacrylate (plasticized soft segment monomer, PPGMA, Mn 375), and 0.04 g of hydroxy-cyclohexyl phenyl ketone (photoinitiator 184), stir well until homogeneous to form a precursor solution. Put the well-mixed precursor solution into a vacuum chamber with a vacuum degree of 0.1 bar and degas for 30 s. Inject the degassed precursor solution into the assembled glass slide-silicone pad-PTFE sandwich cavity. Place the mold with the injected precursor solution in an ultraviolet cross-linking box with a power density of 50 mW / cm 2 , polymerize for 30 min. After the reaction is completed, disassemble the silicone pad mold, take out the sample and place it in a vacuum drying oven. Under vacuum at 80 °C, degas for 12 h to remove residual volatile monomers, obtaining a low surface energy and high adhesion polymer adhesive, which is stored at room temperature in a desiccator for later use.
[0057] Example 3
[0058] This example provides an adhesive, and its preparation method is as follows:
[0059] Mix 3.4 g of tetrafluoropropyl methacrylate (fluorinated hard segment monomer, TFOMA), 0.6 g of poly(propylene glycol) methacrylate (plasticized soft segment monomer, PPGMA, Mn 375), and 0.04 g of 1-hydroxy-cyclohexyl phenyl ketone (photoinitiator 184), stir well until homogeneous to form a precursor solution. Put the well-mixed precursor solution into a vacuum chamber with a vacuum degree of 0.1 bar and degas for 30 s. Inject the degassed precursor solution into the assembled glass slide-silicone pad-PTFE sandwich cavity. Place the mold with the injected precursor solution in an ultraviolet cross-linking box with a power density of 50 mW / cm 2 , polymerize for 30 min. After the reaction is completed, disassemble the silicone pad mold, take out the sample and place it in a vacuum drying oven. Under vacuum at 80 °C, degas for 12 h to remove residual volatile monomers, obtaining a low surface energy and high adhesion polymer adhesive, which is stored at room temperature in a desiccator for later use.
[0060] Example 4
[0061] This example provides an adhesive, and its preparation method is as follows:
[0062] 3.2 g of dodecafluoroheptyl methacrylate (fluorinated hard segment monomer, DFOMA), 0.8 g of poly(propylene glycol) methacrylate (plasticized soft segment monomer, PPGMA, Mn 375), and 0.04 g of 1-hydroxy-cyclohexyl phenyl ketone (photoinitiator 184) were mixed and stirred thoroughly until homogeneous to form a precursor solution. The well-mixed precursor solution was placed in a vacuum chamber with a vacuum degree of 0.1 bar and degassed for 30 s. The degassed precursor solution was injected into an assembled glass slide-silicone gasket-PTFE sandwich cavity. The mold with the injected precursor solution was placed in an ultraviolet cross-linking box with a power density of 50 mW / cm 2 , and polymerized for 30 min. After the reaction ended, the silicone gasket mold was disassembled, the sample was taken out and placed in a vacuum drying oven, and vacuum degassed at 80 °C for 12 h to remove residual volatile monomers, obtaining a low surface energy and high adhesion polymer adhesive, which was stored at room temperature in a desiccator for standby.
[0063] Example 5
[0064] This example provides an adhesive, and its preparation method is as follows:
[0065] 3.6 g of trifluoroethyl methacrylate (fluorinated hard segment monomer, TFEMA), 0.4 g of poly(propylene glycol) methacrylate (plasticized soft segment monomer, PPGMA, Mn 375), and 0.04 g of 1-hydroxy-cyclohexyl phenyl ketone (photoinitiator 184) were mixed and stirred thoroughly until homogeneous to form a precursor solution. The well-mixed precursor solution was placed in a vacuum chamber with a vacuum degree of 0.1 bar and degassed for 30 s. The degassed precursor solution was injected into an assembled glass slide-silicone gasket-PTFE sandwich cavity. The mold with the injected precursor solution was placed in an ultraviolet cross-linking box with a power density of 50 mW / cm 2 , and polymerized for 30 min. After the reaction ended, the silicone gasket mold was disassembled, the sample was taken out and placed in a vacuum drying oven, and vacuum degassed at 80 °C for 12 h to remove residual volatile monomers, obtaining a low surface energy and high adhesion polymer adhesive, which was stored at room temperature in a desiccator for standby.
[0066] Example 6
[0067] This example provides an adhesive, and its preparation method is as follows:
[0068] Mix 3.6 g of hexafluorobutyl methacrylate (fluorinated hard segment monomer, HFBMA), 0.4 g of methoxypolyethylene glycol methacrylate (plasticized soft segment monomer, PEGMMA, Mn 300), and 0.04 g of 1-hydroxy-cyclohexyl phenyl ketone (photoinitiator 184), and stir well until homogeneous to form a precursor solution. Place the well-mixed precursor solution in a vacuum chamber with a vacuum degree of 0.1 bar and degas for 30 s. Inject the degassed precursor solution into the assembled glass slide-silicone gasket-PTFE sandwich cavity. Place the mold with the injected precursor solution in a UV cross-linking box with a power density of 50 mW / cm 2 , and polymerize for 30 min. After the reaction is completed, disassemble the silicone gasket mold, take out the sample, and place it in a vacuum drying oven at 80 °C for vacuum degassing for 12 h to remove residual volatile monomers, obtaining a low surface energy and high adhesion polymer adhesive, which is stored at room temperature in a desiccator for standby.
[0069] Example 7
[0070] This example provides an adhesive, and its preparation method is as follows:
[0071] Mix 3.6 g of hexafluorobutyl methacrylate (fluorinated hard segment monomer, HFBMA), 0.4 g of methoxypolyethylene glycol methacrylate (plasticized soft segment monomer, PEGMMA, Mn 475), and 0.04 g of 1-hydroxy-cyclohexyl phenyl ketone (photoinitiator 184), and stir well until homogeneous to form a precursor solution. Place the well-mixed precursor solution in a vacuum chamber with a vacuum degree of 0.1 bar and degas for 30 s. Inject the degassed precursor solution into the assembled glass slide-silicone gasket-PTFE sandwich cavity. Place the mold with the injected precursor solution in a UV cross-linking box with a power density of 50 mW / cm 2 , and polymerize for 30 min. After the reaction is completed, disassemble the silicone gasket mold, take out the sample, and place it in a vacuum drying oven at 80 °C for vacuum degassing for 12 h to remove residual volatile monomers, obtaining a low surface energy and high adhesion polymer adhesive, which is stored at room temperature in a desiccator for standby.
[0072] Example 8
[0073] This example provides an adhesive, and its preparation method is as follows:
[0074] Mix 3.6 g of hexafluorobutyl methacrylate (fluorinated hard segment monomer, HFBMA), 0.4 g of polyethylene glycol methyl ether methacrylate (plasticized soft segment monomer, PEGMMA, Mn 950), and 0.04 g of 1-hydroxy-cyclohexyl phenyl ketone (photoinitiator 184), and stir well until homogeneous to form a precursor solution. Place the well-mixed precursor solution in a vacuum chamber with a vacuum degree of 0.1 bar and degas for 30 s. Inject the degassed precursor solution into an assembled glass slide-silicone pad-PTFE sandwich cavity. Place the mold filled with the precursor solution in a UV cross-linking box with a power density of 50 mW / cm 2 , and polymerize for 30 min. After the reaction is completed, disassemble the silicone pad mold, take out the sample, and place it in a vacuum drying oven. Under 80 °C, vacuum degas for 12 h to remove residual volatile monomers, obtaining a low surface energy and high adhesion polymer adhesive, which is stored at room temperature in a desiccator for standby.
[0075] Comparative Example 1
[0076] Mix 4 g of butyl methacrylate (hard segment monomer, BMA) and 0.04 g of 1-hydroxy-cyclohexyl phenyl ketone (photoinitiator 184), and stir well until homogeneous to form a precursor solution. Place the well-mixed precursor solution in a vacuum chamber with a vacuum degree of 0.1 bar and degas for 30 s. Inject the degassed precursor solution into an assembled glass slide-silicone pad-PTFE sandwich cavity. Place the mold filled with the precursor solution in a UV cross-linking box with a power density of 50 mW / cm 2 , and polymerize for 30 min. After the reaction is completed, disassemble the silicone pad mold, take out the sample, and place it in a vacuum drying oven. Under 80 °C, vacuum degas for 12 h to remove residual volatile monomers, obtaining a low surface energy and high adhesion polymer adhesive, which is stored at room temperature in a desiccator for standby.
[0077] Comparative Example 2
[0078] This comparative example provides an adhesive, and its preparation method is as follows:
[0079] Mix 4.0 g of hexafluorobutyl methacrylate (fluorinated hard segment monomer, HFBMA) and 0.04 g of hydroxy-cyclohexyl phenyl ketone (photoinitiator 184), and stir well until homogeneous to form a precursor solution. Place the well-mixed precursor solution in a vacuum chamber with a vacuum degree of 0.1 bar and degas for 30 s. Inject the degassed precursor solution into an assembled glass slide-silicone pad-PTFE sandwich cavity. Place the mold filled with the precursor solution in a UV cross-linking box with a power density of 50 mW / cm 2, Polymerize for 30 min. After the reaction is completed, disassemble the silicone pad mold, take out the sample, and place it in a vacuum drying oven. Under 80 °C, degas it under vacuum for 12 h to remove the residual volatile monomers, obtaining a low surface energy and high adhesion polymer adhesive, which is stored at room temperature in a desiccator for standby.
[0080] Comparative Example 3
[0081] Mix 3.6 g of butyl methacrylate (hard segment monomer, BMA), 0.4 g of poly(propylene glycol) methacrylate (plasticized soft segment monomer, PPGMA, Mn 375), and 0.04 g of 1-hydroxy-cyclohexyl phenyl ketone (photoinitiator 184), stir well until homogeneous to form a precursor solution. Put the well-mixed precursor solution into a vacuum chamber with a vacuum degree of 0.1 bar and degas for 30 s. Inject the degassed precursor solution into the assembled glass sheet-silicone pad-PTFE sandwich cavity. Place the mold with the injected precursor solution in an ultraviolet crosslinking box with a power density of 50 mW / cm 2 , Polymerize for 30 min. After the reaction is completed, disassemble the silicone pad mold, take out the sample, and place it in a vacuum drying oven. Under 80 °C, degas it under vacuum for 12 h to remove the residual volatile monomers, obtaining a low surface energy and high adhesion polymer adhesive, which is stored at room temperature in a desiccator for standby.
[0082] Comparative Example 4
[0083] Mix 3.6 g of hexafluorobutyl methacrylate (fluorinated hard segment monomer, HFBMA), 0.4 g of butyl acrylate (soft segment monomer, BA), and 0.04 g of 1-hydroxy-cyclohexyl phenyl ketone (photoinitiator 184), stir well until homogeneous to form a precursor solution. Put the well-mixed precursor solution into a vacuum chamber with a vacuum degree of 0.1 bar and degas for 30 s. Inject the degassed precursor solution into the assembled glass sheet-silicone pad-PTFE sandwich cavity. Place the mold with the injected precursor solution in an ultraviolet crosslinking box with a power density of 50 mW / cm 2 , Polymerize for 30 min. After the reaction is completed, disassemble the silicone pad mold, take out the sample, and place it in a vacuum drying oven. Under 80 °C, degas it under vacuum for 12 h to remove the residual volatile monomers, obtaining a low surface energy and high adhesion polymer adhesive, which is stored at room temperature in a desiccator for standby.
[0084] Comparative Example 5
[0085] 4.0 g of poly(propylene glycol) methacrylate and 0.04 g of hydroxy-cyclohexyl phenyl ketone (photoinitiator 184) were mixed and stirred thoroughly until homogeneous to form a precursor solution. The well-mixed precursor solution was placed in a vacuum chamber with a vacuum degree of 0.1 bar and degassed for 30 s. The degassed precursor solution was injected into an assembled glass sheet-silicone pad-PTFE sandwich cavity. The mold filled with the precursor solution was placed in an ultraviolet cross-linking box with a power density of 50 mW / cm 2 , and polymerized for 30 min. After the reaction ended, the silicone pad mold was disassembled, and the sample was taken out and placed in a vacuum drying oven. Under 80 °C, it was vacuum degassed for 12 h to remove residual volatile monomers. However, poly(propylene glycol) methacrylate could not be effectively polymerized, resulting in a low surface energy and high adhesion polymer adhesive with no bonding strength.
[0086] The adhesives obtained in the examples and comparative examples were characterized. The main test method was lap-shear test. The test contents included the change of lap-shear strength at different times in a high humidity environment, the comparison of lap-shear strength of the polymer adhesive on different substrates, and the influence of different feed ratios on the enhancement effect of lap-shear strength. Figure 1 shows the influence of different monomer feed ratios on lap-shear strength (hexafluorobutyl methacrylate hard segment and poly(propylene glycol) methacrylate soft segment, where the PPGMA content is 0%, 15% and 40% corresponding to Comparative Example 2, Example 1 and Example 2 respectively). The results show that with the increase of the soft segment monomer, the adhesion performance of the polymer adhesive first reaches a peak and then decreases; Figure 2 shows the relationship between different fluorinated hard segment monomers and lap-shear strength (including Examples 3-5). Even when different fluorinated hard segment monomers are selected, the polymer adhesive still shows good adhesion performance on PTFE substrates, reflecting the universality of this system; Figure 3 shows the relationship between different plasticized long molecular chain soft segment monomers and lap-shear strength (including Examples 6-8). The results show that the length of the side chain molecular chain is proportional to the adhesion performance within a certain range; Figure 4 is the comparison of lap-shear strength of the polymer adhesive in Example 1 on different low surface energy substrates; Figure 5 is the change of lap-shear strength of the material in Example 1 in a 90% relative humidity environment. The results show that this polymer adhesive has good moisture resistance. Figure 6 and Figure 7 is the distribution of fluorinated groups in the AFM-IR test material and the bonding interface in Example 1, explaining the adhesion mechanism between the polymer adhesive and the bonding interface: among them Figure 6 (i), (ii), (iii) and Figure 7(i), (ii), and (iii) are respectively the surface topography structures of the non-bonding surface of the material and the bonding surface with the PTFE substrate, the chemical mapping of the non-bonding surface of the material scanned by AFM-IR at the specific infrared wavelength of the C-F group, and the chemical mapping of the non-bonding surface of the material scanned by AFM-IR at the specific infrared wavelength of the C-F group. The results show that there is a high energy distribution at the interface where the material is bonded to the PTFE, indicating that the C-F groups will gradually migrate and aggregate at the interface bonded to the PTFE during the adhesion process, confirming the dipole-dipole interaction at the interface between the material and the adhesive, and providing the adhesion energy for the polymer adhesive; Figure 8 The test results of ultraviolet-visible spectrophotometry show the high transparency (93.72%) of the adhesive obtained in Example 1, indicating good miscibility of the polymer chains; Figure 9 is the lap-shear strength of the BMA and PPGMA copolymer adhesive on the PTFE substrate. The highest strength is only about 0.5 MPa, which indirectly proves that the C-F groups in the fluorinated monomer have a strong interaction with the PTFE substrate (including Comparative Examples 1 and 3); Figure 10 is the lap-shear strength of the HFBMA and BA copolymer adhesive on the PTFE substrate (including Comparative Example 4). The highest strength is about 1 MPa, which is still much lower than the bonding strength of the HFBMA and PPGMA copolymer adhesive. Therefore, it can be proved that the side-chain friction effect of PPGMA makes a great contribution to adhesion.
[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application and are not intended to limit them; although the present application has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. An adhesive with high adhesion strength for low surface energy materials, characterized in that, It includes a fluorinated hard segment and a long polymer chain soft segment with a plasticizing effect; The fluorinated hard segment monomers corresponding to the fluorinated hard segment include fluorinated methacrylate monomers; the soft segment monomers corresponding to the long polymer chain soft segment with a plasticizing effect include polyether-type methacrylate monomers.
2. The adhesive with high adhesion strength for low surface energy materials according to claim 1, characterized in that, The fluorinated hard segment monomers include one or more of hexafluorobutyl methacrylate, trifluoroethyl methacrylate, tetrafluoropropyl methacrylate, pentafluorobenzyl methacrylate, hexafluoroisopropyl methacrylate, heptafluorobutyl methacrylate, octafluoropentyl methacrylate, nonafluorohexyl methacrylate, dodecafluoroheptyl methacrylate, tridecafluorooctyl methacrylate, perfluoroalkyl ethyl methacrylate, perfluorooctyl methacrylate, 2-[(1',1',1'-trifluoro-2'-(trifluoromethyl)-2'-hydroxy)propyl]-3-norbornene methacrylate; Preferably, the soft segment monomers include one or more of poly(propylene glycol) methacrylate, methoxypolyethylene glycol methacrylate, methoxypolyethylene glycol acrylate, polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, tetraethylene glycol monomethacrylate, polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate, poly(ethylene glycol) methacrylate, ethoxylated trimethylolpropane triacrylate.
3. The adhesive with high adhesion strength to low surface energy materials according to claim 2, characterized in that, The mass ratio of the fluorinated hard segment monomers to the soft segment monomers is 1-9:1, preferably 17:
3.
4. The adhesive with high adhesion strength to low surface energy materials according to any one of claims 1-3, characterized in that, The number average molecular weight range of the adhesive is 26,887 g / mol to 2,688,700 g / mol.
5. A method for preparing an adhesive having high adhesion strength to low surface energy materials according to any one of claims 1-4, characterized in that, It includes: Mixing the fluorinated hard segment monomers, the soft segment monomers and an initiator to obtain a precursor liquid; Performing a polymerization reaction on the degassed precursor liquid, and then performing vacuum drying to obtain the adhesive.
6. The preparation method of the adhesive with high adhesion strength for low surface energy materials according to claim 5, characterized in that, The initiator includes a photoinitiator and / or a thermal initiator; The photoinitiator includes one or more of 1-hydroxy-cyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,4,6(trimethylbenzoyl) diphenyl phosphine oxide, 2,4,6-trimethylbenzoyl phosphonic acid ethyl ester, 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone, 2-isopropyl thioxanthone, ethyl 4-dimethylaminobenzoate, benzoin dimethyl ether, methyl o-benzoylbenzoate, 4-chlorobenzophenone, 4-phenylbenzophenone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, α-ketoglutaric acid; The thermal initiator includes one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptonitrile, dimethyl azobisisobutyrate, 1-(cyano-1-methylethylazo)formamide, 1,1'-azo(cyanocyclohexane), benzoyl peroxide, diisopropylbenzene peroxide, methyl ethyl ketone peroxide, di-tert-butyl peroxide, potassium persulfate, ammonium persulfate.
7. The preparation method of the adhesive with high adhesion strength for low surface energy materials according to claim 6, characterized in that, The dosage of the initiator is 0.01%-10% of the total mass of the fluorinated hard segment monomers and the soft segment monomers, preferably 1%.
8. The preparation method of the adhesive with high adhesion strength to low surface energy materials according to claim 5, characterized in that, The polymerization reaction is photo-initiated, and the conditions for photo-initiation are a light source power density of 1 - 1000 mW / cm 2 , a wavelength of 200 - 450 nm, and a time of 0.01 - 24 h; Or; The polymerization reaction is thermal initiation, and the temperature of the thermal initiation is 40-110 °C and the time is 1-72 h; Alternatively, the polymerization reaction is carried out by the immersion method.
9. The preparation method of the adhesive with high adhesion strength for low surface energy materials according to any one of claims 5-8, characterized in that, One or more of the following conditions are satisfied: (1) The conditions for degassing are: vacuum degree 1 - 20 kPa, time 0.1 - 10 min; (2) The conditions for vacuum drying are: vacuum degree 0.1 - 1000 Pa, temperature 20 - 100 °C, time 18 - 24 h; (3) The storage conditions for the adhesive are: relative humidity not higher than 60%, temperature -50 °C to 60 °C.
10. Use of an adhesive having high adhesion strength to a low surface energy material according to any one of claims 1-4, characterized in that, It is used for bonding low surface energy materials.
Citation Information
Cited By
OCA optical cement composition and preparation method thereof
CN121182410A